1999
DOI: 10.1002/(sici)1521-3935(19991101)200:11<2448::aid-macp2448>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the thermal aggregation in aqueous poly(N-isopropylacrylamide-co-itaconic acid) solutions

Abstract: SUMMARY: Copolymers of N-isopropylacrylamide (NIPAAM) and itaconic acid (IA) were prepared via free radical polymerisation using potassium persulfate (K 2 S 2 O 8 ) in distilled-deionised water at 50 8C in nitrogen atmosphere. The dependence of the aggregation process on pH and IA content and the copolymer composition were examined by means of UV-VIS, FTIR, and 1 H NMR spectroscopy, gel permeation chromatography (GPC), and viscosity measurements. Cloud points of 0.5 wt.-% aqueous solutions of the copolymers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Also, the intensity of the carbonyl peak belonging to the carboxyl group of IA increases with increasing IA content in the feed. Furthermore, the intensities of the other bands related with both NIPAAm (-NH bending at 1540 cm À1 , -C ¼ O stretching for secondary amides at 1660 cm À1 , and isopropyl group at 1385 and 1370 cm À1 ) and IA (-CH 2 group adjacent to the carbonyl group of IA at about 1495 cm À1 and hydrogen bonded hydroxyl in the 2500-2700 cm À1 region) confirm the copolymers structure [42,43].…”
Section: Polymer Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the intensity of the carbonyl peak belonging to the carboxyl group of IA increases with increasing IA content in the feed. Furthermore, the intensities of the other bands related with both NIPAAm (-NH bending at 1540 cm À1 , -C ¼ O stretching for secondary amides at 1660 cm À1 , and isopropyl group at 1385 and 1370 cm À1 ) and IA (-CH 2 group adjacent to the carbonyl group of IA at about 1495 cm À1 and hydrogen bonded hydroxyl in the 2500-2700 cm À1 region) confirm the copolymers structure [42,43].…”
Section: Polymer Characterizationmentioning
confidence: 99%
“…The LCST of copolymer at high pH values is even higher. At higher pH values, temperature-sensitivity is not seen over the range of temperatures studied because ß-COOH of IA is completely ionized [47].…”
Section: Thermoresponsive Behavior Of Polymersmentioning
confidence: 99%
“…The synthesis conditions of these samples are reported elsewhere. 13 It is known that both polymerization rates and intrinsic viscosities of itaconate polymers are low because of degradative chain transfer to monomer. 14±16 For this reason, the intrinsic viscosities determined in 0.34 g 100 ml À1 15 mM phosphate buffer in normal saline (pH = 7.4) of PIA ([Z] = 0.41 dl g À1 ) and PNIPAAM-IA copolymers containing 75.3 and 52.1 mole% IA ([Z] = 0.49 dl g À1 and [Z] = 0.72 dl g À1 , respectively) synthesized in this work are much lower than that of PNIPAAM ([Z] = 3.19 dl g À1 for t = 2 h) although the reaction times are long (48 h and 24 h for PIA and its copolymers, respectively).…”
Section: Polymerization Proceduresmentioning
confidence: 99%
“…9,10 A mechanism for chemical oxidative polymerization of Py by ceric ammonium nitrate, (NH 4 ) 2 [Ce(NO 3 ) 6 ] in the presence of a polyanion or its copolymers has recently been reported by Sarac et al which gives soluble products. 12,13 The aim of this work is to investigate how random copolymers of hydrophobic N-isopropylacrylamide (NIPAAM), which may be used as a model system for simulating the thermal denaturation of biological polymers, and pH-sensitive itaconic acid (IA) increasing the hydrophilic character of the chains, will affect the Py polymerization in aqueous (NH 4…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it acts as a better candidate material for use in drug delivery due to its effective CR characteristics for many drugs under the influence of temperature. It has been reported that incorporation of hydrophilic/hydrophobic comonomers into PNIPAAm hydrogels will change its swelling characteristics as well as other physicochemical properties, including mechanical strength and solute diffusivity 13–19. The phase transition temperature of PNIPAAm matrix occurs at or near the physiological temperature, i.e., 37°C 20.…”
Section: Introductionmentioning
confidence: 99%